Pengaruh Citra Merek dan Kualitas Produk terhadap Kepuasan Pelanggan: Studi Kasus pada Jersey Tim Nasional Indonesia Merek ERSPO - Muhammad Zaki Al Hakim; Endang Mahpudin (Journal of Management and Creative Business, 2026)
This study explores the influence of brand image and product quality on customer satisfaction in the context of ERSPO, the official brand of the Indonesian National Football Team jersey. The sports industry, particularly football, has a large fan base in Indonesia, making the national team jersey an important symbol of national identity and pride among supporters. Using a quantitative research method, data were collected through questionnaires distributed to 51 respondents who were ERSPO customers. This study tested three main hypotheses: (1) brand image has a significant effect on customer satisfaction, (2) product quality has a significant effect on customer satisfaction, and (3) brand image and product quality simultaneously have a significant effect on customer satisfaction. Multiple linear regression analysis, along with validity, reliability, and classical assumption tests, was employed to analyze the data. The findings contribute to the development of marketing theory by examining the relationships among these variables within the specific context of the sports industry. Furthermore, the results provide valuable insights for ERSPO and the sports industry in formulating effective marketing and production strategies to enhance customer satisfaction and loyalty.